Promoting cessation in hospitalized smoking patients: a systematic review - Amaral,Lígia Menezes do (2020)
SUMMARY OBJECTIVES The objective of this review was to evaluate high intensity post-discharge follow-up strategies to promote smoking cessation in hospitalized patients. METHODS A systematic review was performed, based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA – P) protocol. The databases used for research were: PubMed, LILACS/BIREME, Scopus, Web of Science, Cochrane and Scielo. The included articles were randomized clinical trials, published from 1990 to 2018, which evaluated in-hospital and post-discharge intervention, and provided a minimum of 30-day care post discharge. The studies aimed to evaluate tobacco cessation. RESULTS Fourteen studies were selected for analysis. Across studies, pharmacotherapy was consistently effective for smoking cessation. Communication technologies likewise were consistently effective for cessation and post-discharge access. CONCLUSION Effective strategies exist. The challenge for future trials is to determine the best approaches for different clinical contexts, to promote cessation.